Релаксационные потери в полиэтиленовой изоляции кабелей коаксиальной конструкции в условиях повышенной влажности - Беспрозванных, А.В.; Кессаев, А.Г. (Електротехніка і електромеханіка, 2016)
Выполнены измерения в диапазоне частот 50 кГц – 20 МГц тангенса угла диэлектрических потерь образцов силового и
радиочастотного коаксиального кабелей в исходном состоянии и после увлажнения в условиях 100% влажности. После
старения установлено появление дополнительных релаксационных максимумов для сплошной термореактивной и термопластичной полиэтиленовой изоляции, что обусловлено группированием свободной воды в кластеры соответствующей формы и фрактальной размерности. Для кабелей со вспененной термопластичной полиэтиленовой изоляцией в не
состаренном состоянии присуще проявление релаксационных потерь за счет наличия воды в газообразных включениях.
Установлена положительная корреляция между шириною полосы релаксационных максимумов и скоростью уменьшения сопротивления изоляции от приложенного высокого постоянного напряжения. Виконано вимірювання в діапазоні частот 50 кГц – 20 МГц тангенсу кута діелектричних втрат зразків силового та
радіочастотного коаксіального кабелів в початковому стані та після зволоження в умовах 100% вологості. Після
старіння встановлено появу додаткових релаксаційних максимумів для суцільної термореактивної та термопластичної поліетиленової ізоляції, що обумовлена групуванням вільної води в кластери відповідної форми та фрактальної
розмірності. Для кабелів зі спіненою термопластичною ізоляцією в початковому незістареному стані притаманно
прояв релаксаційних втрат за рахунок наявності води, розташованої в повітряних включеннях. Встановлено додатний кореляційний зв’язок між шириною смуги релаксаційних максимумів та швидкістю зменшення опору ізоляції від
прикладеної високої постійної напруги Introduction. The presence of free moisture in power cables
leading to the formation of tree structures - water treeing, which
originate in the amorphous phase polyethylene and are a major
cause of degradation of the polymer insulation. They represent
the damage of the polymer size from several microns to 1 mm,
developing technology for insulation defects under the combined
action of the electric field and the moisture diffusing from the
environment. Water treeing destroys the polymer chain, resulting in the formation of microcavities filled with moisture. The
dynamics of water treeing and subtle properties largely depend
on the composition, morphology of the polymer insulation,
chemical nature of the defect, in which they originate. Due to
the force of gravity in the water formed typical only for her region with locally ordered structure - clusters, which cause loss
of relaxation. Purpose. Features presence of relaxation losses in
high-frequency range in polyethylene insulation during aging in
high humidity conditions of samples power and RF cables. Methodology. Samples of the power cable for the voltage of 35 kV
with a cross-linked polyethylene insulation radial waterblocking protection from moisture and radio-frequency coaxial
cable with thermoplastic insulation for 1440 hours in a humidity
of 100%. The dielectric loss tangent measured resonance method before and after aging. Originality. Experimentally found
evidence of the existence in the polymer cable insulation free
water in the form of areas with locally ordered structure - clusters. It is found that the solid polyethylene insulation in the frequency dependence of dielectric loss tangent maximum relaxation shown one at 10 MHz in the initial state, and there are two
additional frequency range 500 kHz - 5 MHz after moistening.
For cross-linked polyethylene insulation characteristic of large
width Δf of the frequency spectrum in which the observed relaxation losses. It is obvious that the width of each of the relaxation maxima is associated with characteristic fractal cluster
size. It is important that the hydrated solid and foamed polyethylene insulation to show individuality, typical only for water
clusters which are detected by high-frequency dipole relaxation
peaks dielectric loss tangent. There is a positive correlation
between the bandwidth Δf of relaxation maxima and the rate of
decrease of insulation resistance by applying a high DC voltage.
Practical value. Establishing a correlation between the bandwidth of relaxation maxima and the rate of decrease in the insulation resistance test objects in the laboratory makes it possible
to diagnose the presence of free moisture in the power and RF
cables by measuring the insulation resistance in exploitation.